Journey of the jihadist inside Muslim militancy - Gerges, Fawaz A. 1958- (Harcourt, 2006)
Middle Eastern expert and media commentator Gerges takes us into the mindset of the jihadi, or holy warrior, that lies behind so many front-page headlines yet remains nearly impenetrable. Even before the 9/11 attacks, Gerges had gone in search of those whose lives were devoted to this crusade of hatred, first against their own secular governments, then against the West and the United States in particular. He talked extensively with Kamal al-Said Habib, a founder of the Jihadist Movement. Using Habib?s life story, as well as the stories of dozens of other Islamic fundamentalists, Gerges?s book puts a human face to events in the Middle East over the last thirty years, from the civil war in Lebanon to the war in Iraq and the terrorist attacks in London. Behind the jihadism of Habib and others, a battle is being waged for the soul of Islam itself.--From publisher description.